1979
DOI: 10.1172/jci109340
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin-Releasing Hormone is not Required for Thyrotropin Secretion in the Perinatal Rat

Abstract: A B S T R A C T To determine the role of thyrotropinreleasing hormone (TRH) in the regulation of thyroidstimulating hormone (TSH) secretion in the perinatal period, a physiological approach of neutralizing circulating TRH in the fetal andl early neonatal rat was employed. TRH-antiserum (TRH-AS) raised in rabbits and administered daily to low iodine-propylthiouracil (LID-PTU)-fed pregnant rats from days 12 to 19 of gestation markedly impaired the rise in serum TSH to LID-PTU when compared with normal rabbit ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…The first peak of IR-TRH described by these workers may therefore represent TRH bound to either lipid or protein. In addition, the presence of lipids or proteins in the radioimmunoassay could interfere with the binding of iodinated TRH with its antiserum, and result in higher levels ofTRH in blood compared with those reported here in plasma (19,20).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The first peak of IR-TRH described by these workers may therefore represent TRH bound to either lipid or protein. In addition, the presence of lipids or proteins in the radioimmunoassay could interfere with the binding of iodinated TRH with its antiserum, and result in higher levels ofTRH in blood compared with those reported here in plasma (19,20).…”
Section: Discussionmentioning
confidence: 65%
“…Several investigators have demonstrated the presence of low levels of TRH in the blood and plasma of the adult rat (16)(17)(18), and more recently, higher concentrations have been found in the blood of the fetal and neonatal rat (19,20). The reasons for the differences in the circulating levels of TRH at different periods of development of the rat have not been established.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tonooka et al (21) reported that serum TSH concentrations in encephalectomized fetus was markedly elevated when pregnant rats were fed PTU and that hypothalamic lesions in these PTU-fed pregnant rats did not prevent the TSH rise in the fetus. Theodoropoulos et al (20) treated neonatal hypothyroid rats with TRH antiserum and found that this treatment was ineffective in decreasing serum TSH concentrations before the tenth day of life. We have recently observed that exogenous administration of TRH during the neonatal period leads to a significant increase in serum TSH concentration, which can be impaired in a dose-dependent fashion by treatment of the neonatal rat with T3 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Theodoropoulos et al (20) recently presented data which suggest that TRH does not participate in TSH regulation during the first 10 days of postnatal life. Their results were primarily based on the lack of effect of TRH antiserum in suppressing fetal and neonatal TSH secretion.…”
Section: Discussionmentioning
confidence: 99%